The epidemiology of platelet transfusions: an analysis of platelet use at 12 US hospitals. Issue 1 (18th December 2019) - Gottschall, Jerome; Wu, YanYun; Triulzi, Darrell; Kleinman, Steven; Strauss, Ronald; Zimrin, Ann Butler; McClure, Christopher; Tan, Sylvia; Bialkowski, Walter; Murphy, Edward; Ness, Paul; ,
Abstract: BACKGROUND: Using the Recipient and Donor Epidemiology Study‐III (REDS‐III) recipient and donor databases, we performed a retrospective analysis of platelet use in 12 US hospitals that were participants in REDS‐III. STUDY DESIGN AND METHODS: Data were electronically extracted from participating transfusion service and blood center computer systems and from medical records of the 12 REDS‐III hospitals. All platelet transfusions from 2013 to 2016 given to patients aged 18 years and older were included in the analysis. RESULTS: There were 28, 843 inpatients and 2987 outpatients who were transfused with 163, 719 platelet products (103, 371 apheresis, 60, 348 whole blood derived); 93.5% of platelets were leukoreduced and 72.5% were irradiated. Forty‐six percent were transfused to patients with an International Classification of Diseases, 9th/10th Revision (ICD‐9/10) diagnosis of leukemia, myelodysplastic syndrome (MDS), or lymphoma. The general ward and the intensive care unit (ICU) were the most common issue locations. Only 54% of platelet transfusions were ABO identical; and 60.6% of platelet transfusions given to Rh‐negative patients were Rh positive. The most common pretransfusion platelet count range for inpatients was 20, 000 to 50, 000/μL, for outpatients it was 10, 000 to 20, 000/μL. Among ICU patients, 35% of platelet transfusion episodes had a platelet count of greater than 50, 000/μL; this was only 8% for general ward and 2% for outpatients. The median posttransfusion increment, not corrected for platelet dose and/or patient size, ranged from 12, 000 to 20, 000/μL for inpatients, and from 17, 000 to 27, 000/μL for outpatients. CONCLUSIONS: These data from one of the largest reviews of platelet transfusion practice to date provide guidance for where to focus future clinical research studies and platelet blood management programs.